The witch's wand : the craft, lore & magick of wands & staffs - MacLir, Alferian Gwydion, 1960- (Witch's tools series, 2015)
The lore, history, and symbolism of the wand; how to make your own for different uses or occasions; and lots of wand spells and rituals are included in this book.